Intended to Fail? Jatropha Development Project in Indonesia - Tristam P. Moeliono (Bina Nusantara University, 2016)
Article offers an analytical description of the legal framework of the Indonesian biofuel energy policy : commercialization of Jatropha. Its purpose is to explain why the legal framework failed. Methodology used to collect data is library research, including shifting through related legal documents. Additional information was collected through interviews with key informants. The purpose is to be able to place the relevant legal framework within a broader economic-political context. The main findings were that government intervention in the economic sector (commercialization of Jatropha), were made more in the spirit of poverty eradication programs and lessening government financial burden in providing cheap fossil fuel. Cautious approach based on economic calculations and other considerations (Jatropha not being sufficiently tested and developed as biofuel crop) as advised by researchers (2006) working under the auspices of the Ministry of Agriculture were simply ignored.